Origem e ramificação do nervo frênico em suínos (Sus scrofa domesticus Linnaeus, 1758) da linhagem Pen Ar Lan - Penna Neto, Abelardo Moreira dos Santos (2018)
World pig farms have been developing steeply due to advances in genetic improvement and this has led researchers to investigate possible anatomical variations in new lineages. The objective was to verify the origin and branching of the phrenic nerve was studied in 27 swine fetuses (sus scrofa domesticus - linnaeus, 1758) of the Pen Ar Lan line, 19 males and 8 females, obtained from abortion or stillbirths, which were dissected after fixation in 10% formaldehyde solution. The referred nerve originated in 51 antimeres (94.4%) of the fifth cervical spinal nerve (C5); in 54 antimeres (100%) of the sixth cervical spinal nerve (C6) and six antimeres (11.11%) of the seventh cervical spinal nerve (C7). Regarding the distribution, the phrenic nerves delivered fibers to the pericardium and then, branched into the diaphragm muscle in 100% of the specimens. Six types of branches were observed, most frequently the dorsal, lateral and ventral branches in 22 antimeres (40.74%), followed by branching in dorsal branches and ventrolateral trunk in 18 antimeres (33.33%), besides that, two ramifications in pig fetuses that were not found in the consulted literature, demonstrating their variability. The dorsal branches were distributed to the pillar muscles of the lumbar part, the ventral branches to the sternal part and the lateral branches to the costal part.